Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.